English reading pedagogical mediation for language basic level students in the Preschool Education course at UNED, Costa Rica (Innovaciones Educativas, 2022)
The need to develop linguistic competencies in a second language in Costa Rica's early childhood has led state universities to review their curricula for teacher training. This reality and the mediation of materials in English as a requirement for accreditation led to the need to incorporate readings in a second language in the different subjects of the Early Childhood Education Program at UNED, knowing that the population lacks proficiency in this language. The intention of this study was to mediate readings in English using strategies based on tasks and cooperative work for graduate students with a basic command of the language. Both strategies were chosen because they were appropriate for distance learning. The material chosen by experts was a reading and a video, which meet the following requirements: 1- the reading: short (no more than 5 pages), simple vocabulary, and illustrative images. 2- the video: short (no more than 4 minutes) and with English subtitles.  The mediation and evaluation of the material were carried out on the platform through prediction activities. The activities evaluated comprehension and listening skills and were presented in an academic forum. It was found that as long as the student population can use all visual, auditory, and prior knowledge resources in the assessment activities, language as such does not represent an obstacle. These results suggest the benefit of the strategy of task work, collaborative work, and predictive activities as techniques to mediate the material in another language.
Keywords: Learning strategies; linguistic attitudes; expressive language; language skills; second language learning; education